Salt stress perception and metabolic regulation network analysis of a marine probiotic Meyerozyma guilliermondii GXDK6 - Cai, Xinghua; Sun, Huijie; Yan, Bing; Bai, Huashan; Zhou, Xing; Shen, Peihong; Jiang, Chengjian (Frontiers in Microbiology, 2023)
Extremely salt-tolerant microorganisms play an important role in the development of functional metabolites or drug molecules. In this work, the salt stress perception and metabolic regulation network of a marine probiotic Meyerozyma guilliermondii GXDK6 were investigated using integrative omics technology. Results indicated that GXDK6 could accept the salt stress signals from signal transduction proteins (e.g., phosphorelay intermediate protein YPD1), thereby contributing to regulating the differential expression of its relevant genes (e.g., CTT1, SOD) and proteins (e.g., Catalase, Superoxide dismutase) in response to salt stress, and increasing the salt-tolerant viability of GXDK6. Omics data also suggested that the transcription (e.g., SMD2), translation (e.g., MRPL1), and protein synthesis and processing (e.g., inner membrane protein OXA1) of up-regulated RNAs may contribute to increasing the salt-tolerant survivability of GXDK6 by improving protein transport activity (e.g., Small nuclear ribonucleoprotein Sm D2), anti-apoptotic ability (e.g., 54S ribosomal protein L1) and antioxidant activity (e.g., Superoxide dismutase). Moreover, up to 65.9% of the differentially expressed genes/proteins could stimulate GXDK6 to biosynthesize many salt tolerant-related metabolites (e.g., β-alanine, D-mannose) and drug molecules (e.g., deoxyspergualin, calcitriol), and were involved in the metabolic regulation of GXDK6 under high NaCl stress. This study provided new insights into the exploration of novel functional products and/or drugs from extremely salt-tolerant microorganisms.